THE IMPORTANCE AND RELEVANCE OF STYLISTICS IN LINGUISTICS (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This paper examines the theoretical foundations of stylistic analysis, underlining its conceptual orientation and linguistic characteristics. As a subfield of linguistics, stylistics studies how (and why) language use varies according to different contexts (with a focus on phonetic, lexical, grammatical, semantic, and pragmatic features). It discusses the main approaches to stylistic analysis: formalist, functional, cognitive, and corpus stylistics. It also emphasizes typing style devices like alliteration, metaphor, and irony, forming the meaning of the text and the perception of the reader. These investigations highlight the relevance of stylistic investigation in both literary and non-literary discourse and show how such work can uncover abstract linguistic and communicative functions.